Hubungan Pengetahuan dan Motivasi Perawat terhadap Pelaksanaan Early Warning System (EWS) di Rumah Sakit Swasta di Indonesia Tengah - Agri Cristia Ratag; Lia Kartika (JURNAL KEPERAWATAN RAFLESIA, 2021)
Early Warning Score (EWS) is a request system to address current patient health problems that based on patients’ assessment of physiological parameter changes through systematic observation. Inconsistent implementation of the EWS can put patient safety at risk. This study aims to determine the relationship between knowledge and motivation of nurses on the implementation of EWS in the treatment room at a private hospital in central Indonesia. This research was a quantitative descriptive correlational study with a cross-sectional approach. The sample selection technique used an overall sample technique totaling 54 people in one private hospital in central Indonesia from March to April 2019. Chi square test analysis identified that there was no statistically significant relationship between knowledge and EWS implementation (p = 0.161). The analysis also showed that there was no statistically significant relationship between motivation and EWS implementation (p=0.101). Further research can identify factors that influence nurses' knowledge and motivation towards EWS as well as factors that support the implementation of a comprehensive EWS in an inpatient setting.